Get the answers you've been searching for with IDNLearn.com. Our experts are ready to provide in-depth answers and practical solutions to any questions you may have.
Sagot :
Answer:
tan²Θ
Step-by-step explanation:
simplify the expression using the identities
secΘ = [tex]\frac{1}{cos0}[/tex]
tan²Θ = sec²Θ - 1
then
[tex]\frac{cos0-cos^30}{cos^30}[/tex] ( divide each term on the numerator by cos³Θ
= [tex]\frac{cos0}{cos^30}[/tex] - [tex]\frac{cos^30}{cos^30}[/tex]
= [tex]\frac{1}{cos^20}[/tex] - 1
= sec²Θ - 1
= tan²Θ
Answer:
[tex]\tan^2(\theta)[/tex]
Step-by-step explanation:
Assuming this is
[tex]\dfrac{\cos(\theta)-cos^3(\theta)}{cos^3(\theta)}[/tex]
Trig identities used:
[tex]\sin^2(\theta)+\cos^2(\theta)=1 \implies 1-\cos^2(\theta)=\sin^2(\theta)[/tex]
[tex]\dfrac{\cos(\theta)-cos^3(\theta)}{cos^3(\theta)}[/tex]
[tex]=\dfrac{\cos(\theta)(1-cos^2(\theta))}{cos^3(\theta)}[/tex]
[tex]=\dfrac{1-cos^2(\theta)}{cos^2(\theta)}[/tex]
[tex]=\dfrac{sin^2(\theta)}{cos^2(\theta)}[/tex]
[tex]=\tan^2(\theta)[/tex]
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Discover the answers you need at IDNLearn.com. Thanks for visiting, and come back soon for more valuable insights.